2013, the Peruvian Chemistry Olympiad (OPQ) grows up - Chong, Miguel (2013)
The Peruvian Chemistry Olympiad celebrates its 18th birthday with good results in the international competitions in Russia (45th International Chemistry Olympiad, IChO), where two of our students were awarded with bronze medals, and in Bolivia (18th Olimpiada Iberoamericana de Química, OIAQ), where each one of them managed to reach a bronze medal.